Kumbang Koksi sebagai Ide dalam Penciptaan Karya Seni Grafis Teknik Cut Out Stencil Print - Zahra, Syilvi Amalia; Ariusmedi, Ariusmedi (TSAQOFAH, 2025)
Ladybugs (Coccinellidae) are small insects often associated with a charming image, yet they play two contrasting roles in the ecosystem. This study explores the duality of the ladybug’s character through a series of visual works using the Cut Out Stencil Print technique, portraying it both as a beneficial natural pest control agent and as a potentially disruptive species if its population becomes uncontrolled. The resulting artworks combine ecological messages with strong visuals, contrasting colors, and engaging compositions, emphasizing the ladybug’s role as a protector of chili plants from aphids and, conversely, as a nuisance capable of causing irritation or invading homes during the rainy season. The creative process involved idea exploration, sketching, cutting, and coloring, all directed toward reinforcing the visual narrative. The findings affirm that despite its small size, the ladybug plays a vital role in maintaining ecosystem balance. This work invites the public to be more sensitive to human–nature relationships and to consider natural pest control solutions over chemical-based approaches.